Transforming Chitosan into N-Doped Carbon for Efficient CO2 Capture: A comprehensive Review - Celca Rahmatunnisa; Raudhatul Islam Chaerun; Canggih Setya Budi; Noto Susanto Gultom (Applied Surface Science Advances)
Carbon dioxide (CO₂) emissions contribute significantly to global warming, and hence the development of an efficient carbon capture system is essential. This review article explores the prospects of N-doped carbon materials derived from chitosan for CO₂ capture. Chitosan is a nitrogen-rich, easily biodegradable biopolymer that can be used as an ideal precursor for the production of N-doped carbon materials with tuned porosity and high surface area. The nitrogen content increases the adsorption performance by creating active sites for chemisorption and physisorption, while hierarchical pore structures optimize CO₂ diffusion and retention. Further enhancements in material performance are introduced with innovations in chemical activation and nitrogen-enriched additives. We comprehensively review the existing method for transforming chitosan into N-doped carbon materials for carbon capture applications. This study concludes that these sustainable materials possess great significant potential for industrial-scale CO₂ capture and mitigation, aligning with sustainable development goal SDGs 13: Climate Action. Future research should focus on optimizing the synthesis methods, enhancing the functional stability, and integrating this material in the form of beads rather than powder. These efforts aim to significantly improve both effectiveness and sustainability for large-scale and real-world applications.